Republic of Kazakhstan : Technical Assistance Report-Risk-Based Supervision Recovery Plans and Interest Rate Risk. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
This virtual technical assistance (TA) mission supported the Agency in strengthening certain elements of its risk-based supervisory framework. The mission provided recommendations and training to the Agency on the assessment of banks' recovery plans and interest rate risk in the banking book (IRRBB). The mission benefited from simultaneous translation. The priorities for the forthcoming TA missions were discussed with the Agency (strengthening cybersecurity in financial institutions, and assessment of banks' liquidity within the SREP framework).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Kazakhstan, Republic of